Fractal monopole antenna for WLAN USB dongle - Q. Luo (2009)
This article presents the design and fabrication of a simple printed fractal monopole antenna for WLAN USB dongle applications. The proposed antenna uses the combination of meander line and fractal geometry, which is very simple and easy to fabricate, to achieve a multiband operation characteristic. The parameters of this antenna were optimized through numerical simulations in Ansoft HFSS, after which the antenna has been fabricated and characterized. The measurement results show that the proposed antenna has a -10 dB return loss bandwidth of 2.22 to 2.52 GHz and 5.03 to 5.84 GHz, which covers the entire required band for WLAN 802.11a/b/g standards. Moreover, from the simulation results, it is also observed that this proposed antenna exhibits constant gain of 1.8 dBi with 95% radiation efficiency in the lower band and 2.4 dBi with 94% radiation efficiency in the upper band, respectively.